Socialization of green logistics on wire waste management as a commercial plate basket product - Lolyka Dewi Indrasari; Ana Komari; Afiff Yudha Tripariyanto; Jamilatus Sa'idah (Universitas Muhammadiyah Magelang, 2022)
Utilization of wire waste is feasible to be produced as a plate basket product. The partner who has implemented this innovation is UKM Putu Alwy Jaya. The community service team conducted socialization with the topic